The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.30703/cije.915897
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Augmented and Virtual Reality Applications in E-Learning on Students' Use of Microscopes

Abstract: History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…< 0.05). It can therefore be concluded that the use of AR-based learning media can enhance students' understanding of mechanical wave content, as supported by previous researches [3,[21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: B Results Of the Experimental Stagesupporting
confidence: 61%
See 1 more Smart Citation
“…< 0.05). It can therefore be concluded that the use of AR-based learning media can enhance students' understanding of mechanical wave content, as supported by previous researches [3,[21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: B Results Of the Experimental Stagesupporting
confidence: 61%
“…The previous researches [1][2] found that AR can strengthen students' understanding of concepts and personality. In line with [3,7,[27][28][29][30][31][32][33][34][35][36][37], AR can improve learning and cognitive skills [24][25][26], personal skills and social skills [1,28,38].…”
Section: Literature Reviewmentioning
confidence: 94%
“…VR environment in terms of learners' perceptions and their conceptual learning in Physics learning increased (Georgiou et al, 2020;Tsivitanidou et al, 2021). The use of virtual reality technology in the e-learning environment had a positive effect on students (Abdüsselam & Erten, 2022;Rogers et al, 2017;Wiederhold et al, 2018;F. Yang & Wu, 2010).…”
Section: Discussionmentioning
confidence: 97%